A phase II, randomized, double‐blind, placebo‐controlled, dose‐ranging study to evaluate the efficacy and safety of VT‐1161 oral tablets in the treatment of patients with distal and lateral subungual onychomycosis of the toenail. (13th July 2020) - Elewski, B.; Brand, S.; Degenhardt, T.; Curelop, S.; Pollak, R.; Schotzinger, R.; Tavakkol, A.
Summary: Background: Onychomycosis is a fungal disease that affects the fingernails and toenails and is predominantly caused by dermatophytes. VT‐1161 is a novel inhibitor of fungal CYP51 through the inhibition of lanosterol demethylase, and has demonstrated potent activity against Trichophyton rubrum and Trichophyton mentagrophytes . Objectives: To evaluate the safety and efficacy of four dosing regimens of orally administered VT‐1161 compared with placebo in patients with moderate‐to‐severe distal and lateral subungual onychomycosis of the toenail. Methods: This was a phase II, randomized, double‐blind, placebo‐controlled, multicentre study (ClinicalTrials.gov identifier NCT02267356). Patients aged 18–70 years ( n = 259) who had 25–75% mycotic involvement were randomized to five treatment groups. They received 300 mg VT‐1161 as a 2‐week daily dose, followed by a once‐weekly dose for either 10 or 22 weeks, or 600 mg VT‐1161 as a 2‐week daily dose, followed by a once‐weekly dose for either 10 or 22 weeks. All treatments were followed by a nontreatment period of 36 weeks. A matching placebo arm was included. Results: In the intent‐to‐treat population, at week 48 the complete cure rates were 0% in the placebo group and ranged from 32% to 42% in the VT‐1161 treatment groups ( P < 0·001 vs. placebo). VT‐1161 was well tolerated, with no evidence of an adverse effect on liver function or QT intervals. Conclusions: VT‐1161 treatment led to high nail clearance rates and a favourable safety profile. VT‐1161 exhibits characteristics that appear promising for the treatment of this chronic and difficult‐to‐treat condition and warrants further evaluation in larger studies. Abstract : What is already known about this topic? Onychomycosis is a fungal disease that is chronic and difficult to treat. Topical drugs are currently available but have limited effectiveness. Oral drugs, while effective, suffer from side‐effects including liver function abnormalities. The majority of patients are elderly on polypharmacy and are at high risk of drug interactions. An effective and safe oral drug with low potential for liver toxicity and drug interaction is highly desirable. What does this study add? This study presents the first large phase II study of a novel tetrazole antifungal, VT‐1161. The study shows that VT‐1161 has an encouraging safety profile and is highly effective in treating even hard‐to-treat cases of onychomycosis. The new tetrazole provides a lower overall drug load with an excellent safety and tolerability profile. VT‐1161 is as effective as or numerically better than the current standard of care, terbinafine. Linked Comment: Barbieri. Br J Dermatol 2021; 184:191 . Plain language summary available online